Elas se divertem (Barbacena - MG, 1914 a 1931) - Igor Maciel da Silva (2023)
The analysis of amusements that focus on women is still not an evident theme in researches of Women’s History and Leisure Studies in Brazil. Through the present dissertation we aimed to comprehend the ways in which women from Barbacena engaged in the amusements from 1914 to 1931. Specifically, we intended to point out amusements current in the city during the time studied; to identify what were the amusements in which women engaged and which women were those; to comprehend how women had fun, with whom, where and how they engaged in these amusements; to investigate which were the senses and meanings given to those practices; and, finally, to interpret what was adviced and censored related to the amusements and to the engaging of women from Barbacena. For such, the newspaper Cidade de Barbacena was constituted as a main source. It was considered as the main one of the region, along with other sources as O Sericicultor, Olympic Jornal, memory reports, dictionaries, annuals, and almanacs. The data analysis was based into two main categories: Cine-Theaters and Corporal Practices. In summary, we verified that the Barbacena women participated in the amusements as spectators, planners, and members. Spectators attending film sessions, various artistic presentations, soccer games, horse riding parades and competitions. Organizers of charity events that included theatrical, literary, musical, dance and cinema presentations. Members of amusements plans as amateurs which included theatrical, literary and musical artistic shows, in soccer teams in the position of sponsors, in athletic practices as competitors, in skating and dance, in horse riding parades representation, in scouting and as Queen and Gran-Duchess in the footing on 15 de Novembro street, among other activities. The Barbacena women of wealthiest classes were the prominent ones in mobilized sources, however many evidences show participation or requests for participating by women from other classes, as the poor ones. Primary teachers had a prominent role in the schedules of amusements. Besides spectators and members of artistic shows, they were also promoters and planners of entertainment, which implies that being a teacher in the analysed time and in Barbacena context was something that permitted the transit of women in several places of that society.